Computer methods to locate signals in nucleic acid sequences. - Staden, R (1984)
This paper describes computer methods for locating signals in nucleic acid sequences. The signals include ribosome binding sites, promoter sequences and splice junctions. The methods are of use both to those trying to interpret the function of newly determined sequences and to those studying the molecular mechanisms involved in the recognition of these special signal sequences.